[en] HYPERBOLIC COXETER GROUPS - HELLEN ANGELICA DA SILVA ALMEIDA (MAXWELL, 2018)
[pt] Grupos de Coxeter ou de reflexões são importantes no estudo de inúmeras áreas da matemática, incluindo grupos e álgebras de Lie. Nesta dissertação apresentaremos a teoria básica de grupos de reflexões e a classificação dos grupos hiperbólicos, i.e., daqueles que agem no espaço hiperbólico tendo como domínio fundamental um politopo compacto. === [en] Groups of Coxeter or of reflections they are important in the study of countless areas of the mathematics, including groups and algebras of Lie. In this dissertation we will present the basic theory of groups of reflections and the classification of the hyperbolic groups, this is of those that act in the hyperbolic space tends as fundamental domain a compact politopo.